2009
DOI: 10.2166/wst.2009.711
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bio-recalcitrant organics removal by combined adsorption and ozonation

Abstract: Removal of bio-recalcitrant and toxic compounds from wastewaters has been a major objective of industrial manufacturers for a few years. Due to the potential risk toward public health, regulations are becoming increasingly strict and classical treatments like biological treatments are not efficient. Other techniques such as incineration, oxidation or adsorption provide higher levels of removal but with a high energy and capital cost. A coupled process involving adsorption and oxidation is studied. Four adsorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Several authors have shown interesting removal efficiencies when activated carbons are used to decompose gaseous ozone. However, a degradation of activated carbon structure has also been proven . Hence, materials that are more resistant have to be found.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have shown interesting removal efficiencies when activated carbons are used to decompose gaseous ozone. However, a degradation of activated carbon structure has also been proven . Hence, materials that are more resistant have to be found.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, materials that are more resistant have to be found. Metal oxides such as manganese or silver oxides have been reported to be very efficient in ozone decomposition . Nevertheless, the performances of such materials are strongly limited due to their low active surface.…”
Section: Introductionmentioning
confidence: 99%
“…Merle et al concluded that using adsorption and ozone compounds such as 2,4-dichlorophenol and nitrobenzene would be capable of decomposing compounds within the system, where activated carbon had a suitable adsorbent and decomposition of ozone [27]. Wang et al concluded that by using a biofilter with ozone concluded that the chlorobenzene had the capability to increase by 50% when the ozone concentration increased to 120 mg/m 3 [28].…”
Section: Physicochemical Treatmentmentioning
confidence: 99%
“…The application of advanced oxidation processes can consequently be necessary to improve oxidation yields of resistant organic matter (Bailey 1978;Jans and Hoigné 1998). Catalytic ozonation appears to be an interesting solution as a tertiary treatment to create less selective and more oxidant species thanks to solid catal ys ts (Baig and Mouchet 2010;Merle et al 2009), among them the TOCCA T N catalytic process (Fontanier et al 2006). Like any surface catal ys is phe nomenon in a three-phase medium, catalytic ozonation undergoes five main physicochemical phenomena: ozone transfer from the gaseous phase to the liquid phase, diffusion of dissolved molecules (ozone and organic matter) towards the active sites of the catal ys t surface, followed by adsorption of both dissolved ozone and organic species, chemical reaction(s) onto the catal ys t surface and finally desorption of reaction pro ducts.…”
Section: Introductionmentioning
confidence: 99%